INTEGRATION OF OPERATIONAL AUDIT AND ACCOUNTING INFORMATION SYSTEM IN WORKING CAPITAL FINANCING: SYSTEMATIC LITERATURE REVIEW - Wahyu Wibowo; Trinandari Prasetya Nugrahanti (Bajang Institute, 2025)
This study investigates the integration of operational audit and accounting information systems (AIS) to enhance the effectiveness of working capital credit financing. Amid increasing inefficiencies in credit allocation and internal controls, this research addresses the growing need for a data driven, accountable financing system. Employing a Systematic Literature Review (SLR) method, 14 peer reviewed articles from 2010-2025 were analyzed. The findings reveal that integrated audits and AIS significantly improve data accuracy, decision making speed, and risk management. The synthesis highlights key factors such as audit independence, system reliability, and top management support as critical to successful implementation. However, challenges like resource limitations and resistance to change persist. This study contributes a comprehensive framework illustrating how synergy between audit and AIS can optimize credit management, improve financial performance, and strengthen stakeholder trust. Future research is encouraged to explore industry specific case studies and the application of emerging technologies such as AI and data analytics in integrated audit systems